2016
DOI: 10.1177/2158244016643141
|View full text |Cite
|
Sign up to set email alerts
|

Using the Delphi Technique to Identify Key Elements for Effective and Sustainable Visitor Use Planning Frameworks

Abstract: Protected areas around the world receive nearly 800 billion visits/year, with international tourism continuing to increase. While protected areas provide necessary benefits to communities and visitors, the increased visitation may negatively impact the resource and the recreational experience, hence the need to manage visitor use in protected areas around the world. This research focused on obtaining information from experts to document their experiences utilizing one visitor use planning framework: Visitor Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…The Delphi technique uses multiple rounds of questionnaires to transform experts’ ideas into group consensus (Sekayi & Kennedy ). This study was conducted in three rounds, which is similar to other studies (Fefer et al ). The Delphi technique was further modified so that individual interviews were conducted in place of open‐ended survey questions for the first round (Keeney et al ) to gain insight about participation strategies in policy development.…”
Section: Methodsmentioning
confidence: 82%
“…The Delphi technique uses multiple rounds of questionnaires to transform experts’ ideas into group consensus (Sekayi & Kennedy ). This study was conducted in three rounds, which is similar to other studies (Fefer et al ). The Delphi technique was further modified so that individual interviews were conducted in place of open‐ended survey questions for the first round (Keeney et al ) to gain insight about participation strategies in policy development.…”
Section: Methodsmentioning
confidence: 82%
“…21 The Delphi Technique is a method designed to attain consensus of ideas of a group of experts (via) a series of intensive surveys interspersed with controlled belief feedback. 22 Many studies support its to develop and inform curriculum, thus, this technique have been found useful in curriculum development in business, nursing, medicine, agriculture, and technology along with environmental education. 23 In addition, numerous studies endorse the use of Delphi technique in pharmacy curriculum foundation.…”
Section: Baclgroundmentioning
confidence: 99%
“…This technique was chosen for two reasons. First, it has proved to be useful in areas where there is uncertainty, a lack of empirical evidence, and is dealing with complex issues [46,47] such as sustainability [48]. Especially when, exploring complex issues necessitates the need to develop a consensus [49,50], and knowledge from experts who are familiar with this specific issue [47], as they help to achieve this goal.…”
Section: Why Delphi Technique?mentioning
confidence: 99%